A method of determining structural stress for fatigue strength evaluation of welded joints based on notch stress strength theory. (September 2016) - Shen, Wei; Yan, Renjun; Barltrop, Nigel; Liu, Enqian; Song, Lifei
Highlights: A new method was proposed to evaluate the structural stress in welded joints. A modified methodology for fatigue strength assessment was described. Several structural stress approaches were described and discussed. Validity of this method is further verified by the fatigue test results in literatures. Abstract: This paper presents a new method to evaluate the structural stress in welded joints. The method is based on notch stress strength theory, 1 mm stress method and the 'equivalent zero point' stress method. According to notch stress strength theory, a simple method with the singularity strength ' as ' is used to estimate the stress field distribution at the corner. Moreover, a modified methodology for fatigue strength assessment, has been developed, starting from a cruciform model, and then further developed to realistic ship structural components. Validity of this method is further verified by analyzing the stress results for several typical welded joints reported in literature. The results show that the proposed method has the additional advantage in simplified fatigue strength estimation for welded joints and it is able to account for the thickness effect observed in welded joints.